Data for "Direct genetic effects, maternal genetic effects and maternal genetic sensitivity on prenatal heat stress for calf diseases and corresponding genomic loci in German Holsteins" - Yin, Tong; Justus Liebig University Giessen (My University, 2022)
The aim of this study was to infer the effects of heat stress (HS) during late gestation of dams on direct and maternal genetic parameters for pneumonia (PNEU, 112,563 observations), diarrhea (DIAR, 176,904 observations) and omphalitis (OMPH, 176,872 observations) in Holstein calves kept in large-scale co-operator herds. The genotype dataset included 41,135 SNPs from 19,247 male and female cattle. Temperature-humidity indices (THI) during the last eight weeks of pregnancy were calculated, using the climate data from the nearest public weather station for each herd. Heat load effects were considered for average weekly THI larger than 60, and THI lower than 60 were treated equally. Phenotypically, regression coefficients of calf diseases on prenatal THI during the last eight weeks of gestation were estimated in eight consecutive runs. Strongest detrimental effects on PNEU and DIAR due to prenatal HS were identified for the last week of pregnancy (WK1). Thus, only WK1 was considered in ongoing genetic analyses. In an advanced model considering prenatal HS, random regression coefficients on THI in WK1 nested within maternal genetic effects (maternal slope effects for heat load) were considered to infer maternal sensitivity in response to prenatal THI alterations. Direct heritabilities from the advanced model ranged from 0.10 (THI 60) to 0.08 (THI 74) for PNEU, and were close to 0.16 for DIAR. Maternal heritabilities for PNEU increased from 0.03 to 0.10 along the THI gradient. For DIAR, the maternal heritability was largest (0.07) at the minimum THI (THI = 60), and decreased to 0.05 at THI 74. Genetic correlations smaller than 0.80 for PNEU and DIAR recorded at THI 60 with corresponding diseases at THI 74 indicate genotype by climate interactions for maternal genetic effects. Genome-wide associations studies (GWAS) were performed using de-regressed proofs of genotyped sires for direct genetic, maternal genetic and maternal slope effects. 30 suggestive and 2 significant SNPs were identified from GWAS. 43 genes located close to the suggestive SNPs (±100 kb) were annotated as potential candidate genes. Three biological processes were inferred on the basis of the identified potential candidate genes, addressing the negative regulation of the viral life cycle, innate immune response and protein ubiquitination. Hence, genetics of prenatal heat stress mechanisms are associated with immune physiology and disease resistance mechanisms.